Non-cardiomyocytes in the heart in embryo development, health, and disease, a single-cell perspective - Ding, Shuangyuan; Zhang, Xingwu; Qiu, Hui; Wo, Jiaoyang; Zhang, Fengzhi; Na, Jie (Frontiers in Cell and Developmental Biology, 2022)
Recent single-cell atlases of the heart gave unprecedented details about the diversity of cell types and states during heart development in health and disease conditions. Beyond a profiling tool, researchers also use single-cell analyses to dissect the mechanism of diseases in animal models. The new knowledge from these studies revealed that beating cardiomyocytes account for less than 50% of the total heart cell population. In contrast, non-cardiomyocytes (NCMs), such as cardiac fibroblasts, endothelial cells, and immune cells, make up the remaining proportion and have indispensable roles in structural support, homeostasis maintenance, and injury repair of the heart. In this review, we categorize the composition and characteristics of NCMs from the latest single-cell studies of the heart in various contexts and compare the findings from both human samples and mouse models. This information will enrich our understanding of the cellular basis of heart development and diseases and provide insights into the potential therapeutic targets in NCMs to repair the heart.